Teaching Vocabulary For Esp Students - Zakirova Dilorom Yuldashevna (Research Parks Publishers, 2021)
In foreign language learning, vocabulary is one of the important language components that make its basis. Possessing worth vocabulary helps learners to well understand spoken and written discourse. One can not communicate a foreign language without having sufficient amount of words. However, learners may face various problems when encountering unfamiliar words, especially when it comes to remembering, they tend to forget almost new words if they are presented merely verbally and in non-motivated situations